Perge 2010 - ABBASOĞLU, Haluk (Anadolu Akdenizi Arkeoloji Haberleri / News of Archaeology from Anatolia's Mediterranean Areas, 2011)
Excavation carried out in Building Z situated in the first insula of the north-south main street of Perge. Room no. 5 is paved with opus sectile, terracotta plaques and opus tessellatum mosaic. Maintanence work carried out in rooms no. 1, 2 as well as the upper floor of the grave chamber designated M9, in parcel no. 169 situated on the western necropolis. Mosaics have been revealed, consolidated and buried again in order to assure better preservation.
p. 82-89 (résumés turc et anglais).
Keywords: Bibliographie par pays, région ou ensemble géographique; Édifice (Pergè, TUR) Z; Conservation; Insula (Pergè, TUR); Carrelage; Nécropole (Pergè, TUR); Opus sectile; Aksu